Do Women Comply More than Men? Experimental Evidence from a General Population Sample - Müge Süer; Nicola Cerutti; Jana Friedrichsen; Gyula Seres (CESifo GmbH, 2024)
Women are often perceived as more compliant than men; however, the literature provides inconclusive evidence. Using a novel experimental design comprising two complementary experiments, we test this claim in online samples representative of the German adult population. The first experiment (N=1600) features a probabilistic social dilemma game (PDG) in which participants can increase their individual payoff at the expense of exposing themselves and their group to probabilistic losses. In two treatment conditions, they receive either a recommendation on socially optimal behavior or a recommendation and information on weakly non-compliant peer behavior. We find that the recommendation strongly affects behavior but more so for women than for men. However, information on the non-compliant behavior of others does not induce significantly different responses in men and women. In the second experiment (N=522), we elicit empirical and normative expectations about behavior in the PDG with a recommendation to study the role of norms in following it. While men and women are expected to hold similar normative beliefs, men are expected to follow the recommendation less often, suggesting that compliance is a female social norm.
Keywords: J16; I12; D81; H41; 330; compliance; public good; social dilemma; gender; risk-taking; social norms